Thermal Degradation and Thermodynamic Properties of Ascorbic Acid, Total Phenolic Content and Antioxidant Activity of Convective Dried Kiwi Fruits - Fadime Begüm Tepe (Turkish Journal of Agriculture: Food Science and Technology)
In the current study, thermal degradation and thermodynamic properties of ascorbic acid, total phenolic content, and antioxidant activity of convective dried kiwi fruits were investigated. To determine kinetic model describing thermal degradation of these parameters, zero order, first order, fractional conversion and Weibull model were used. Weibull model gave the best fitting to thermal degradation of these parameters. Moreover, the rate constant of the thermal degradation reaction increased with the increment in drying temperatures, meaning that these degradation reactions were temperature dependent. On the other hand, total phenolic content had the lowest activation energy and ∆H value indicating the lowest thermal stability in comparison to others. The degradation reactions endothermically occurred during drying process. Additionally, it was seen that the reason for the higher degradation rate at higher temperatures as the absolute values of ∆S increased. It is important to evaluate thermal degradation of bioactive compounds for the design of the thermal processes. This study will be beneficial for the convective drying process design due to these results.